Correlations towards prediction of petroleum fraction viscosities: an empirical approach - (:unkn) unknown (ELSEVIER SCI LTD, 2001)
New empirical correlations have been developed to predict viscosities of petroleum fractions (C-5-C-15) at 40 degreesC under atmospheric pressure. Viscosities, densities and quantitative hydrocarbon analyses of 42 petroleum fractions were experimentally determined. Viscosities were correlated with density and/or average molecular weight data. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: empirical viscosity correlations; petroleum fractions; CRUDE-OIL FRACTIONS; LIQUID HYDROCARBONS; MIXTURES; TEMPERATURE; PRESSURE